R. West-Pavlov, Transcultural Graffiti. Diasporic Writing and the Teaching of Literary Studies. Prikaz - Šesnić, Jelena (Array, 2005)
A review critically examines West-Pavlov's crucial concepts taken from structuralism, deconstructive criticism and postcolonial studies, namely, transculturation, translation, postcolonial hybridity and diasporic writing. The novelty is the way he proposes that these practices be used in the context of a multicultural teaching context (e.g, in non-native English surroundings) where they can begin to influence the received understanding of these terms.